SELECTION OF POSSIBLE SCENARIOS FOR IMPROVING THE QUALITY OF PUBLIC TRANSPORT SERVICES THROUGH THE USE OF HYBRID FUZZY-MCDM MODELS - Shohreh MORADI; Grzegorz SIERPIŃSKI; Houshmand MASOUMI (Scientific Journal of Silesian University of Technology. Series Transport)
A unified calculating approach is needed for public passenger transportation. All public transport companies and other stakeholders would have additional opportunities to create a transport offer if the unified methodology was made available to them and if calculations and calculation criteria were harmonized. Thus, the main goal – improving citizen mobility – would be accomplished. For this reason, in the study, we suggested the hybrid fuzzy methods for evaluating and improving the quality of public transport service. Unreliable responses of survey participants often distort group decision-making regarding the problem of public services, negatively affecting the end of the calculation procedure. Fuzzy multicriteria decision-making approach has been used. The suggested technique has the advantage of taking into account the degree of fuzzification of respondents' judgments about the choice scenario, while also using two MCDM models to eliminate bias in the responses.